A new route for fabricating polymer optical microcavities. Issue 12 (13th March 2019) - Zhang, Zhang; Yao, Ni; Pan, Jing; Zhang, Lei; Fang, Wei; Tong, Limin
Abstract : SU-8 microcavities with an ultra-smooth surface and high Q factors are demonstrated by using a simple and low cost self-assembly method. Abstract : By using a self-assembly method, SU-8 whispering gallery mode optical microcavities with an ultra-smooth surface ( σ < 0.6 nm) and high- Q factors (∼10 4 ) are fabricated. As an application of the microcavities, we demonstrate a polydimethylsiloxane packaged temperature sensor with high sensitivity (120 pm per °C) and long-term stability (over one year). These results illustrate broad application potential in ultrasensitive sensors and microlasers.